Smallwood Interview 01B - Memorial University of Newfoundland. Educational Television Centre (Memorial University of Newfoundland. Educational Television Centre, 1983)
Smallwood discusses with Robert Pitt why he started collecting books and his lifetime of collecting, writing, and producing books. Smallwood speaks proudly of his collection of 1400 Newfoundland books. Although the subject matter continues, this video is not a continuation of the interview by Cathy Boak on interview 01A.